Inhibition of glycosphingolipid biosynthesis: application to lysosomal storage disorders. - Butters, T; Dwek, R; Platt, F (ACS, 2000)
A review is given on some of the more recent knowledge of the enzymes involved in the control of glycosphingolipids biosynthesis and how catabolic deficiency leads to the glycosphingolipidoses. Focus is on how small-molecule inhibitors have been instrumental in probing the enzymes in these pathways and how their application has been taken from discovery in the laboratory to therapeutic use in man.